Self-efficacy as a moderator of the relationship between emotional exhaustion and psychological well-being of Filipino child care workers in residential centers - Mata, Kimberly Kaye C. (Animo Repository, 2018)
The study investigated the moderating role of self-efficacy on emotional exhaustion and psychological well-being. The role of self-efficacy on emotional exhaustion and psychological well-being was investigated in a sample of 100 Filipino Child Care Workers working in residential centers. Result suggests that they have moderate levels of emotional exhaustion, high levels of psychological well-being, and self-efficacy. Further, findings show that using hierarchical multiple regression, emotional exhaustion (first step analysis) negatively predicted psychological well-being when self-efficacy is not included in the interaction (β= -.352, t(98)= -3.728, p<.05). The second step of regression included self-efficacy which positively predicted psychological well-being and was also found to be statistically significant (β= .475, t(97)= 5.665, p<.05). Despite the significant main effects, analysis shows that there is a non-significant interaction between emotional exhaustion and self-efficacy which indicates that self-efficacy cannot moderate the relationship between the independent and the dependent variable, psychological well-being. Further, self-efficacy is independently affecting psychological well-being. The results confirm that, emotional exhaustion impacts child care workers in a negative manner while having more positive perceptions embodied by self-efficacy heightens the perception of psychological well-being.